CHOOSING A COMPETITIVE STRATEGY FOR THE COMPANY: THE MAIN MISTAKES AND CONSEQUENCES - N. Barkova; J. Trubetskikh (Вестник университета)
To date, the world market includes many companies and to get into, and even more so to stay among the world leaders is quite difficult for the company. In the course of many years of world practice, a number of basic rules have been worked out, which in most cases lead the company to success, but at the same time a number of basic mistakes in the choice of the company’s competitive strategy have been identified. In this article we consider such marketing errors of large companies. In order to answer the question of why such situations occur, the article describes the reasons for making such errors on enterprises by specific examples, the logic of large firms in choosing a competitive strategy is investigated.